2006
DOI: 10.1001/archderm.142.9.1123
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic Patterns of Acral Melanocytic Nevi and Melanomas in a White Population in Central Italy

Abstract: To investigate the dermoscopic features of acral melanocytic lesions in a white population in central Italy.Design: Retrospective review.Setting: University dermatology department.Patients: Six hundred fifty-one Italian subjects, ranging in age from 6 months to 78 years. Main Outcome Measures:We retrospectively investigated all digital dermoscopic images of acral melanocytic lesions included in our database from January 1996 to May 2005. Results:We retrieved digital images of 723 benign acral melanocytic lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
96
5
13

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 23 publications
(57 reference statements)
15
96
5
13
Order By: Relevance
“…5 Our group recently demonstrated that such dermoscopic classifications of acral melanocytic nevi also apply to a white population in central Italy. 6 We also described a transition pattern, observed in benign acral melanocytic nevi on the lateral aspect of the fingers, that combines specific dermoscopic features of volar and nonglabrous skin. 6 Even for experienced dermatologists, acral melanocytic nevi may be difficult to differentiate from early acral melanoma by clinical evaluation alone.…”
mentioning
confidence: 75%
“…5 Our group recently demonstrated that such dermoscopic classifications of acral melanocytic nevi also apply to a white population in central Italy. 6 We also described a transition pattern, observed in benign acral melanocytic nevi on the lateral aspect of the fingers, that combines specific dermoscopic features of volar and nonglabrous skin. 6 Even for experienced dermatologists, acral melanocytic nevi may be difficult to differentiate from early acral melanoma by clinical evaluation alone.…”
mentioning
confidence: 75%
“…Globüler patern 4 1,7 6,12,13,16,18 . Bizim çalışmamızda bu patern diğer çalışmalara göre daha yüksek bir oranda %8,9 olarak tespit edildi.…”
Section: Gereç Ve Yöntemunclassified
“…Altamura ve ark. yaptıkları iki ayrı çalışmada %3,5 ve %1,8 oranında geçiş paternini tespit etmişlerdir 6,16 . Özellikle akral bölgelerin yan kısımlarında görülen bu paternde lezyonun bir tarafında paralel oluk paterni ya da kafes benzeri patern saptanırken, diğer alanlarda tipik pigment ağı saptanır.…”
Section: Gereç Ve Yöntemunclassified
See 2 more Smart Citations